MENINGKATKAN KECAKAPAN LITERASI BACA TULIS MELALUI KEPEMIMPINAN DEMOKRATIS KELAS 2 SDN GAYAM 1 - Fitriani, Dyah Ayu (PGSD UNIKA SANTU PAULUS RUTENG, 2023)
Concrete steps are needed to apply a democratic leadership approach in improving the literacy skills of grade 2 elementary school students. This includes engaging teachers, parents and other relevant parties in supporting and implementing relevant learning strategies. The purpose of this research is to find out whether Democratic Leadership can Increase Grade 2 Elementary School Literacy Literacy. The method is an approach used to overcome problems related to the object of research. The research method or approach used in this study is a descriptive qualitative approach. In this method, primary data is collected through observation or interviews. Based on research findings and interviews with Ms. Leni as a class teacher, it can be concluded that the application of democratic leadership in learning literacy has a significant positive impact on improving student skills.